2022
DOI: 10.1186/s13638-022-02193-5
|View full text |Cite
|
Sign up to set email alerts
|

Securing 6G-enabled IoT/IoV networks by machine learning and data fusion

Abstract: The rapid growth of Internet of Things (IoT) and Internet of Vehicles (IoV) are rapidly moving to the 6G networks, which leads to dramatically raised security issues. Using machine learning, including deep learning, to find out malicious network traffic is one of practical ways. Though much work has been done in this direction, we found little investigating the effect of using fused network conversation datasets to train and test models. Thus, this work proposes to check conversation dataset characteristics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…In Lopez-Martin et al, 15 conversation dataset features were analyzed and identified pertinent features with the purpose of enhancing the potentiality of malicious traffic and also improving the malware detection performance significantly.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…In Lopez-Martin et al, 15 conversation dataset features were analyzed and identified pertinent features with the purpose of enhancing the potentiality of malicious traffic and also improving the malware detection performance significantly.…”
Section: Related Workmentioning
confidence: 99%
“…From this result it is inferred that the attack detection time using the LA-HLRW method was found to be comparatively lesser than. 1,2,9 The dynamic attention mechanism employed in the proposed LA-HLRW method integrates the attention function for activating the hidden layer with the purpose of improving the overall LSTM network performance. This in turn not only results in reducing dimensionality reduced network traffic feature matrix but also results in minimum convergence.…”
Section: Performance Analysis Of Attack Detection Timementioning
confidence: 99%
See 3 more Smart Citations